An interregional extension of destination brand equity: From Hong Kong to Europe. (October 2017) - Kim, Seongseop (Sam); Schuckert, Markus; Im, Holly Hyungjeong; Elliot, Statia
Since the 1990s, the Asia-Pacific region's world market share of international travelers has increased, as America's and Europe's shares have fallen. China (People's Republic of China) has become the world's biggest tourism source market with an overseas spend of US$292 billion in 2015, fueling opportunities for the region and beyond. Now, Asia Pacific outbound travel is extending past short-haul interregional travel to long-haul destinations, specifically Europe. To realize this potential, European destinations need a better understanding of the Chinese traveler; their perceptions of destinations, awareness, and loyalty. This study measures the brand equity of Switzerland and Austria as perceived by Hong Kong Chinese tourists. Structural equation modeling results indicate that destination brand image and associations significantly impact brand loyalty, whereas destination awareness does not, contrary to past interregional research findings. Understanding the influence of brand components on overall brand equity supports the efficacy of the brand equity model for interregional destinations.